Rekayasa Sistem Keterbukaan Data Pemerintah untuk Mendukung Transparansi dan Partisipasi Pemerintah Daerah - Ahmad Hamim Thohari; Suhardi; Novianto Budi Kurniawan; Purnomo Yustianto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Openness and transparency in government is now becoming a global movement. Various programs and initiatives have been built toward openness and public participation. Although existing legislation obligates the government to be more open about the data and information, in practice, the process of obtaining government data by Indonesian citizen is still difficult, due to the bureaucracy. Information technology has not been fully utilized for this process. This paper proposes open government data system engineering process that facilitates publication of government data by the government and access to data by citizen. Case study for the research was conducted in Cimahi City, West Java. This paper also demonstrates the adaptation of system engineering methods in the process of software system engineering with the adjustment and mapping of the techniques used in each stage. Result of user acceptance and usability testing shows that the system meets the performance criteria required by users and has good usability score. The survey on public perception about government transparency and participation with support of the system shows an increase of 39.1% compared to initial condition.